Land reforms in South East Asia. - Zahir Ahmed (New Delhi, 1975)
This book is a brief survey of land reform programmes in few selected countries of the Far East. It is based upon field observation, discussions with offcials, public figures and university professors in various sovereign states of the region.
Keywords: "Asia, South eastern Land reform."